Maintaining Academic Resilience Among Senior Students: Strategies for Overcoming Thesis Writing Challenges - Ismaul Fitroh; Moh. Imron Rosidi; Renol Hasan; Tonny Iskandar Mondong (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2026)
Thesis writing is a crucial academic milestone that students must complete as a requirement for earning a bachelor's degree. However, this process frequently poses significant challenges due to academic and psychological obstacles that affect students' motivation and academic progress. This study aims to identify the challenges faced by senior students and the strategies they employ to maintain academic resilience during the thesis writing process. A qualitative approach with a descriptive research design was adopted, conducted within the History Education Program at the Faculty of Social Sciences, Gorontalo State University. Informants were selected through purposive sampling. Data were collected via observation and interviews, then analyzed using an interactive analysis model. Findings reveal that students encounter difficulties in selecting research topics, understanding methodology, accessing scholarly references, and managing psychological stress. Strategies employed include effective time management, active consultation with academic advisors, seeking social support, and sustaining self-motivation. These findings underscore the importance of strengthening academic resilience to support successful thesis completion.